Organizacijski aspekti regulacijskih tijela za zaštitu tržišnog natjecanja - Kristić, Tadija (Array, 2021)
The main task of the contemporary state is to ensure the functioning of the market and to pursue the public interest through independent regulation, which requires the establishment of regulatory agencies. Over time, negative and somewhat mystical bias towards these agencies has occurred in the public. The public administration reform is an integral part of the political programme of any political actor in the Republic of Croatia and regulatory agencies are one of its main targets. A desktop survey that is a base of this paper included individual competition agencies representing one of the three main European organisational models for competition agencies and investigated their characteristics with respect to organization, personnel aspects, and enforcement. The Portuguese competitionauthority has been taken as the representative of Model A – the authority with only one jurisdiction – enforcement of competition rules. The Croatian competition authority was taken as the example of Model B – the authority with dual competence – competition and unfair trading practices. Finally, Model C was analysed on the example of the Spanish competition authority that is responsiblefor the enforcement of competition rules but at the same time for ex-ante regulation in individual sectors. The results of the survey are expected to provide solutions for the best organizational model, and consequently give further evidence of whether an organizational reform of the Croatian Competition Agency would be necessary in the Republic of Croatia.